The Difficulties of Implementing English Instruction in Cambridge Curriculum: Non-English Teachers' View - Alpiansyah, Rizki; Charisma , Dila; Aprianti , Fitri (Verba: Journal of Applied Linguistics, 2024)
The purpose of this study was a) to find out how teachers learn in implementing the Cambridge curriculum for non-English subjects, b) to find out what difficulties non-English teachers experience in implementing English language learning. The method used in this study is a qualitative descriptive research method. The object of this study was SMP Bina Insan Mulia, the subjects of this study were two teachers who taught non-English subjects at SMP Bina Insan Mulia. The instruments used in this study were interviews and documents compiled following the Cambridge curriculum. The results of interviews and analysis of teacher learning plans showed learning methods that implemented the Cambridge curriculum, the difficulties found were related to; problems with teachers' ability to use English; problems with students in their views on non-English subjects that must use English, student interests, the amount of practice, and also self-confidence. From the difficulties found, teachers made the class more interactive and interesting in teaching non-English subjects by using English as a medium of instruction.